Crop response to soils amended with biochar: expected benefits and unintended risks - Subedi, Raghunath; Bertora, Chiara; Zavattaro, Laura; Grignani, Carlo (Italian Journal of Agronomy, 2017)
Biochar (BC) from biomass waste pyrolysis has been widely studied due to its ability to increase carbon sequestration, reduce greenhouse gas emissions, and enhance both crop growth and soil quality. This review summarises the current knowledge of BC production, characterisation, and types, with a focus on its positive effects on crop yield and soil properties vs the unintended risks associated with these effects. Biochar-amended soils enhance crop growth and yield via several mechanisms: expanded plant nutrient and water availability through increased use efficiencies, improved soil quality, and suppression of soil and plant diseases. Yield response to BC has been shown to be more evident in acidic and sandy soils than in alkaline and fine-textured soils. Biochar composition and properties vary considerably with feedstock and pyrolysis conditions so much that its concentrations of toxic compounds and heavy metals can negatively impact crop and soil health. Consequently, more small-scale and greenhouse-sited studies are in process to investigate the role of BC/soil/crop types on crop growth, and the mechanisms by which they influence crop yield. Similarly, a need exists for long-term, field-scale studies on the effects (beneficial and harmful) of BC amendment on soil health and crop yields, so that production guidelines and quality standards may be developed for BCs derived from a range of feedstocks.